Efficient Sonogashira Coupling Reaction Catalyzed by Copper (I) Iodide in the Presence of KF/Al2O3 - Rahman Hosseinzadeh; Maryam Mohadjerani; Rahmatollah Tavakoli (شیمی کاربردی روز, 2009)
We have developed a convenient and efficient method for coupling of aryl iodides and bromides with terminal alkynes. The protocol uses CuI as catalyst, 1, 10-phenanthroline as ligand, KF/Al2O3 as base and toluene as solvent. The method is suitable for the synthesis of functionalized aryl-alkynes.